سفر سے متعلق حدیثِ جبیر كى تخریج وتحقیق اور علامہ البانى كى رائے كا تنقیدى جائزہ : The Authentication and Analysis of the Hadith of Jubayr bin Mut’im on Travel: A Critical Review of the Opinion of Shaykh Albani - Bashir Ahmad Waziristani; Muhammad Siddique (Al Manhal Research Journal, 2025)
Research is an ongoing process that never comes to a halt. In the world of research, evaluating every opinion, reflecting upon it, and critically examining it based on principled foundation is a hallmark of academic integrity. This very approach has refined the knowledge of researchers and strengthened the scholarly tradition.Shaykh Nasir al-Din Albani is regarded as one of the prominent researchers of the 19th century, and his contributions have left a profound impact on the academic world.Regarding the narration of Jubayr bin Mut’im related to travel, Shaykh Albani classified it as “Munkar” in Silsilah al-Ahadith al-Da’ifah. However, since rulings on hadith are based on ijtihad, it is necessary to review and analyze them to upholdthe standard 0f research and rectify any possible errors. The study critically examines Shaykh Albani’s opinion while also providing a detailed analysis of all the chains of the hadith and the criticism and authentication of its narrators. The objective is to clarify the actual status of the hadith and establish a balanced perspective.